Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1177/154405910708600407
|View full text |Cite
|
Sign up to set email alerts
|

Micromolar Fluoride Alters Ameloblast Lineage Cells in vitro

Abstract: Fluorosed enamel is caused by exposure to fluoride during tooth formation. The objective of this study was to determine whether epithelial ameloblast-lineage cells, derived from the human enamel organ, are directly affected by micromolar concentrations of fluoride. Cells were cultured in the presence of fluoride, and proliferation was measured by BrdU incorporation. The effect of 0, 10, or 20 microM fluoride on apoptosis was determined by the flow cytometry apoptotic index. The effects of fluoride on gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
0
46
0
1
Order By: Relevance
“…The impact of fluoride on ALP activity is still controversial and it seems to be dependent on the experimental design. Both up and down modulation have been found after fluoride treatment using osteoblasts (15)(16)(17). In the present study, there were no differences among the control and treated preosteoblasts.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The impact of fluoride on ALP activity is still controversial and it seems to be dependent on the experimental design. Both up and down modulation have been found after fluoride treatment using osteoblasts (15)(16)(17). In the present study, there were no differences among the control and treated preosteoblasts.…”
Section: Discussionmentioning
confidence: 43%
“…* p<0.05; *** p<0.01. (17,21). In addition, other authors showed that fluoride does not induce DNA damage (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following studies were identified for fluoride (Ge et al, 2011;Sun et al, 2011;Wu et al, 2010;Wurtz et al, 2008;Yan et al, 2007). Four used transcriptomics approaches and one proteomics.…”
Section: Hazardmentioning
confidence: 99%
“…The following studies were identified for xenobiotic response (Skipsey et al, 2011;Smith et al, 2004;Zhang et al, 2007). Safeners coordinately induce the expression of multiple proteins and MRP transcripts involved in herbicide metabolism and detoxification in Triticum tauschii seedling tissues.…”
mentioning
confidence: 99%